The detailed classification of the interlobar artery and the artery crossing intersegmental planes in the right upper lobe - Li, Zhikai; Kong, Yuhong; Li, Bowen; Lv, Wenfa; Zhang, Xiaopeng (Frontiers in Oncology, 2023)
Abstract Background: With the prevalence of three-dimensional computed tomography bronchography and angiography (3D-CTBA) and the development of anatomical segmentectomy, several studies have analyzed the branching patterns of peripheral segmental arteries in the right upper lobe (RUL). Nevertheless, the detailed classification of the branching patterns of the interlobar artery and the artery crossing intersegmental planes remains unknown. Thus, we conducted a retrospective study to analyze the variations of the interlobar artery and the artery crossing intersegmental planes in the RUL by using 3D-CTBA. Materials and Methods: A total of 600 patients with ground glass opacity (GGO) who had undergone 3D-CTBA preoperatively at Hebei General Hospital between September 2020 and September 2022 were used for the retrospective study. We reviewed the anatomical variations of the RUL arteries in these patients using 3D-CTBA images. Results: The branching patterns of the RUL artery were classified into the following four categories: Trunk superior (Tr. sup); Tr. sup + interlobar artery; Tr. sup + trunk inferior (Tr. inf); Tr. sup + Tr. inf + interlobar artery. The branching patterns of the interlobar artery were subclassified into four subtypes: posterior ascending artery (A. pos); anterior ascending artery (A. ant); A. pos + A. ant; ascending artery (A. asc). The artery crossing intersegmental planes contains two types: type A, anterior subsegmental artery crossing intersegmental planes (AX1b); type B, recurrent artery crossing intersegmental planes (AX. rec). Conclusions: The variation types of blood vessels in the RUL are complex. This study explored the detailed classification of the interlobar artery and the artery crossing intersegmental planes. It can help thoracic surgeons understand the anatomy variations, accurately locate lesions before the surgery, and effectively plan surgeries.